(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Seasonal allergy is a common allergic reaction in children, mainly observed in summer and spring. Its main causes are allergens in the external environment, in particular, plant dust, blue mold fungi and other factors. This article analyzes the causes, clinical symptoms and treatment methods of seasonal allergies.